2012
DOI: 10.1002/ddr.21006
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Studies on the Antioxidant Activity of Aloin Compared to Doxorubicin in Rats

Abstract: Strategy, Management and Health PolicyEnabling Technology, Genomics, ProteomicsPreclinical ResearchPreclinical Development Toxicology, Formulation Drug Delivery, PharmacokineticsClinical Development Phases I‐III Regulatory, Quality, ManufacturingPostmarketing Phase IV In the present study, the cardiotoxicity of aloin, a naturally occurring anthraquinone glycoside with antiproliferative activity was compared with doxorubicin, a cardiotoxic anthracyline drug, in rats. The antioxidant and iron‐chelating activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Several previous reports suggested that ALM shows antiproliferative and antitumor activity in human hepatoma, lung carcinoma cell, and human gastric carcinoma cells and also has high specificity for neuroectodermal tumors . Aloin (ALN) (Figure 1B), another aloe active compound, is an anthraquinone glycoside with a variety of pharmacological activities and can inhibit tumor growth and angiogenesis and has potential chemotherapeutic properties . Aloe emodin‐8‐glucoside (ALMG) (Figure 1C) is another structural homolog, a glucoside metabolite of aloe emodin, and has shown antidiabetic properties in the treatment of insulin resistance .…”
Section: Introductionmentioning
confidence: 99%
“…Several previous reports suggested that ALM shows antiproliferative and antitumor activity in human hepatoma, lung carcinoma cell, and human gastric carcinoma cells and also has high specificity for neuroectodermal tumors . Aloin (ALN) (Figure 1B), another aloe active compound, is an anthraquinone glycoside with a variety of pharmacological activities and can inhibit tumor growth and angiogenesis and has potential chemotherapeutic properties . Aloe emodin‐8‐glucoside (ALMG) (Figure 1C) is another structural homolog, a glucoside metabolite of aloe emodin, and has shown antidiabetic properties in the treatment of insulin resistance .…”
Section: Introductionmentioning
confidence: 99%
“…This structure was postulated on the basis of in vitro FRAP test, which confirmed the potent reducing potential of aloin (Esmat et al, 2012). In contrast, doxorubicin is a bidentate compound and binds to iron giving rise to Fe 3+ (Dox) 3 complex due to its inability to reduce Fe 3+ to Fe 2+ ions in vitro (Esmat et al, 2012). However, Fe 2+ (Dox) 2 complex might also be formed in vivo due to the prevalence of reducing agents, such as reduced glutathione and NADPH.…”
Section: Discussionmentioning
confidence: 72%
“…A description of Fe 2+ (aloin) 2 complex has been postulated (Figure 4), which shows the binding of Fe 2+ to two molecules of aloin by two types of bonds: an ionic bond at positions 1 or 8 and a coordinating bond at position 9. This structure was postulated on the basis of in vitro FRAP test, which confirmed the potent reducing potential of aloin (Esmat et al, 2012). In contrast, doxorubicin is a bidentate compound and binds to iron giving rise to Fe 3+ (Dox) 3 complex due to its inability to reduce Fe 3+ to Fe 2+ ions in vitro (Esmat et al, 2012).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations